Removing natural latex proteins from dipped rubber goods with fumed silica additives - Shimon Amdur (Rubber Division, American Chemcial Society Orlando, Florida, September 21-24, 1999)
Natural proteins are the main reason for Type 1 latex irritation suffered by sensitive people. About 10;of medical field employees dealing with dipped rubber products suffer from this allergy. This problem has surfaced in the last several years with the increase in production of rubber gloves for protection from infectious diseases. Although natural latex is the best product available for price and performance, bad reputation and litigation potential has caused customers to shy away from it and look for more expensive and mostly inferior substitutes. Obviously many efforts were made to dispose off the proteins, however protein traces may still remain and cause irritation in sensitive people. This paper suggests a way to eliminate the proteins with a simple, elegant and inexpensive method using fumed silica additives. The fumed silica attaches itself to the rubber particle and substitutes the proteins. The proteins are then easily removed. All this can be performed on line, eliminating chlorination and/or extensive washing and handling of the products off line.
Source Year: 2000
Keywords: Dipped rubber goods; Fumed silica; Natural latex proteins